Pediatric epidemiological aspects of scorpionism and report on fatal cases from Tityus stigmurus stings (Scorpiones: Buthidae) in State of Pernambuco, Brazil - Cleide Maria Ribeiro de Albuquerque; Pedro de Lima Santana Neto; Maria Lucineide Porto Amorim; Sofia Campos Vidal Pires (Revista da Sociedade Brasileira de Medicina Tropical, 2013)
Introduction Envenomation by scorpion stings is a major public health problem in numerous tropical countries because of its frequent incidence and potential severity. Approximately 1,900 species of scorpions are known in the world, and at least 130 of these have been described in Brazil. Methods This work reports on 3 child deaths caused by Tityus stigmurus stings and characterizes epidemiological and clinical surveys on pediatric cases of scorpionism recorded in the Centro de Assistência Toxicológica de Pernambuco (Ceatox-PE). Results Scorpion stings accounted for more than 60% of all cases recorded for venomous animals. The children were from 37 cities of the Pernambuco state and accounted for 28.8% of the victims treated for scorpion stings, with the highest incidence in the metropolitan area of Recife. Stings occurred throughout the year and slightly increased during the rainy season. Independent of the elapsed time for a prognosis, most cases showed mild symptoms. Three moderate cases that resulted in death featured cardiogenic shock and/or pulmonary edema or severe neurological symptoms. For the first time, death attributed to T. stigmurus was confirmed by the presence of the scorpion. Conclusions These results suggest that scorpionism in Pernambuco is a public health problem that needs to be monitored carefully throughout the year by the government.